2009
DOI: 10.2528/pier09062702
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Peak Sar in Human Head for Handset Applications With Resistive Sheets (R-Cards)

Abstract: Abstract-In this paper, reduction of peak specific absorption rate (SAR) for handsets with monopole type antenna through R-cards is investigated. While the numerical analysis was performed using finite integration in time domain (FIT), real measurement has been made to validate the simulation results. Both the simulation and measurement results revealed that a minimum SAR Reduction Factor (SRF) of 60% was achieved. The good agreement between the simulation and measurement results has evidenced the effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…It was found that the return loss of the antenna is affected by nearby EM protective sheets. As far as the operating band for the 2.4 GHz WLAN (determined by 11 10 dB S d ) is concerned, the MSHIS-and JCHIS-added antennas can provide a reasonable operating band to cover the desired WLAN band of 2.4-2.484 GHz. However, the operating bands of the metal-plate-added antenna, the R-cardadded antenna, and the RF-absorber-added antenna do not meet the requirement.…”
Section: Configuration Of Electromagnetic Protectivementioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the return loss of the antenna is affected by nearby EM protective sheets. As far as the operating band for the 2.4 GHz WLAN (determined by 11 10 dB S d ) is concerned, the MSHIS-and JCHIS-added antennas can provide a reasonable operating band to cover the desired WLAN band of 2.4-2.484 GHz. However, the operating bands of the metal-plate-added antenna, the R-cardadded antenna, and the RF-absorber-added antenna do not meet the requirement.…”
Section: Configuration Of Electromagnetic Protectivementioning
confidence: 99%
“…For examples, Sager [10] placed a parasitic radiator (metallic plate) between the PIFA and head to reduce the SAR by 6 dB. Chou [11] achieved a minimum SAR reduction factor of 60% for handsets mounted with a monopole antenna through R-cards, Islam [12] found that the peak SAR of the head can be reduced by placing a ferrite sheet between the antenna and head, Kwak [13] designed an electromagnetic band-gap (EBG) component to reduce the SAR by 43%, and Hwang [14] found that the peak SAR in the head can be reduced by placing metamaterials between the antenna and human head. In our previous study [15], highimpedance surfaces (HISs) were proposed to reduce the interaction between a mobile phone antenna and its user, and to reduce SAR values.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, metamaterials, including EBG structures [13], have been proposed for mobile phones with peak SAR descriptions [17]. According to these studies, the overall dimensions of the antennas with metamaterials were larger than those of wireless terminals.…”
Section: Introductionmentioning
confidence: 99%
“…Although, in principle, the solution for general geometries does not require any additional effort with respect to the standard method, the technique requires the definition of a discretised space by assigning to each cell its own electromagnetic properties, which is not an easy process [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation